Planning With 'Three-World Structures': A Comparative Study of Settlements in Mountain Villages - Cut Nuraini; Bhakti Alamsyah; Novalinda; Peranita Sagala; Abdi Sugiarto (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Mountain peoples’ basic understanding of the world is based on binary space concepts such as top-down, left-right, east-west, sacred-profane, and others, which form a threefold division structure that places people in the middle of their environment. Mountain settlements in several places in Indonesia that still emphasize this primitive understanding or classification are interesting to study in terms of their similarities and differences. This study aimed to compare three cases of settlements, namely Singengu Mandailing village in North Sumatra, Tenganan village in Bali, and Kampung Naga in West Java in terms of their understanding of binary space concepts that constitute this threefold division structure and their application in the planning of the community’s living environment. This study is a theoretical dialogue between the concept of binary space (bincar-bonom) in Singengu Mandailing village and two other local concepts that are similar, namely kangin-kauh (sunrise-sunset) in Tenganan village and timur-barat (east-west) in Kampung Naga. This qualitative study used data from the literature and the analysis was carried out following a qualitative descriptive research procedure. Based on previous research, each case has its own data, which the authors used to uncover differences and similarities in the binary space concepts from the three study cases. The authors employed a spatial matrix image to depict the position of each settlement element in the three cases, allowing the similarities and differences to be seen. The findings of the study show that Tenganan, Kampung Naga, and Singengu Mandailing have striking similarities in terms of addressing the middle point, namely as an axis or axis point. The difference lies in the filler elements and their value. The mountain village of Bali interprets the sacred-profane binary concept similarly to the mountain village of Mandailing, except in terms of the direction of sunrise-sunset. The settlement arrangement of Tenganan Pageringsingan village at the macro, meso, and micro scales defines the direction of the sunrise and sunset as a profane direction, whereas in Singengu village, the direction of the sunrise is a sacred direction and the direction of the sunset is a profane direction. As for the Singengu and the Naga communities, they understand the middle point to be related to the direction of the sunrise and sunset in opposite directions, so there are differences in treating certain artifacts, especially cemeteries. The binary space that influences the process of forming rural settlements in the mountains can be: (1) the physical setting due to natural/geographical conditions, (2) the cosmology and belief systems adhered to, and (3) the people’s socio-cultural life. Rural settlements in the mountains can also be said to emphasize the natural aspect of the mountains with all of their spatial shaping potential. The study’s findings further show that the local people’s understanding of their living space patterns has been carried over from previous generations to the present day. This suggests that settlement planning for local communities, particularly in mountainous areas where hereditary beliefs still exist, must be approached in a specific way. In future planning projects, different locations require different planning approaches.